Low-voltage temperature-insensitive logarithmic and exponential function current generators using only npn transistors - Tattaya Pukkalanun; Jetsdaporn Satansup; Sutassa Maneerat; Worapong Tangsrirat; Natchanai Roongmuanpha (EUREKA Physics and Engineering, 2025)
The continuing reduction of supply voltage for reliable operation of analog integrated circuits is widely recognized. Analog circuits must adhere to this trend. As a result, researchers are currently developing low-voltage analog circuit methodologies. Current-mode signal processing circuits are examples of these concepts. Therefore, the objective of this work is to present circuit realizations of low-voltage current-mode logarithmic and exponential function generators with temperature compensation. Both the input and output signals operate in current mode. The design approach utilizes the current-mode translinear technique to produce the output currents that exhibit a directly proportionality to the absolute values of the logarithmic and exponential functions. By simply adjusting the external bias currents, one can electronically tune the output currents and transfer current gains for both proposed circuits. The proposed circuits utilize only npn bipolar transistors and can operate with low-level supply voltages of ±1V, which are appropriate for low-power, high-frequency applications. Nonideality performance considerations are also discussed in detail. In order to verify the operational function of the circuits and illustrate their superior thermal stability, the PSPICE simulation has been performed using real transistor models provided for the HFA3096 mixed bipolar array technology. The simulation findings illustrate that the proposed logarithmic and exponential amplifier circuits can compensate for temperature variations, as evidenced by the good stability of their output currents over a temperature range of -40 °C to 100 °C.
Keywords: Analog and Mixed-Signal Circuit Design; Advancements in Semiconductor Devices and Circuit Design; Low-power high-performance VLSI design